DERIVATIONAL AFFIXATION ON THE STUDENT’S RECOUNT TEXT - Nunur Hasanah; Indra Perdana; Wardani Dwi Wihastyanang (English Teaching Journal : A Journal of English Literature, Language and Education, 2021)
Language is important in our life, especially for communication. Talking about language was certainly lead to the discussion of linguistic, such as morphology. In the morphology there is derivational and inflectional affixation. This thesis focused on analyzing derivational affixation applied in the students’ writing task to find out types of derivational affixation used by the students’ and how is derivational affixation processes in these types. Derivation is the ability to derive new words forms that important to become competence users of English. The researcher interested to analyze derivational affixation in writing skills which is a complicated skill with complete language component to be mastered, such as vocabulary. The researcher chooses writing text from the students because it is interesting to study whether the students’ writing text contain derivational affixation even though they have not received about the material formally. So, the object of this research is writing task produced by the XII-Bahasa students’ at MAN 2 Jombang conducted from the instruction to make a recount text shared through google form. This thesis using qualitative content analysis method. The result of this thesis analyzed according to the theory of Katamba (2006) and Booij (2007), then it shows that the researcher found two types of derivational affixation applied, namely prefixes and suffixes. This research support theory of Katamba (2006) stated that infixes rarely use in English. Then, types of derivational affixation applied on the students’ writing task categorized into their process of derive new words. Prefixes found consist of two kinds in derivational affixation process those are nominal affixation and adjectival affixation. Then, all kinds of derivational affixation process found in suffixes those are nominal affixation, verbal affixation, adjectival affixation and adverbial affixation. To conclude there is many types of derivational affixation applied in the student’s recount text.